Celostna ocena duševnega zdravja in klinično odločanje v napredni zdravstveni negi - Cilar Budler, Leona; Čuček Trifkovič, Klavdija (University of Maribor Press, 2025)
Holistic Mental Health Assessment and Clinical Decision-Making in Advanced Nursing Care. The publication Holistic Mental Health Assessment and Clinical Decision-Making in Advanced Nursing Care explores key aspects of mental health assessment and the clinical decision-making process in nursing care. It emphasizes the use of structured methods, standardized tools, and an interdisciplinary approach in addressing patients with mental health challenges. Special focus is given to specific groups, including children, adolescents, and vulnerable populations, while providing guidelines for advanced nursing practice. The publication aims to enhance healthcare professionals’ competencies in recognizing, assessing, and intervening in mental health issues while supporting clinical decision-making. This publication is intended for nursing professionals seeking to deepen their knowledge and develop a holistic approach to patient mental health care.